Social network analysis for technology-enhanced learning: review and future directions. (23rd January 2013) - Sie, Rory L.L.; Ullmann, Thomas Daniel; Rajagopal, Kamakshi; Cela, Karina; Bitter-Rijpkema, Marlies; Sloep, Peter B.
By nature, learning is social. The interactions by which we learn from others inherently form a network of relationships among people, but also between people and resources. This paper gives an overview of the potential social network analysis (SNA) may have for social learning. It starts with an overview of the history of social learning and how SNA may be of value. The core of the paper outlines the state-of-art of SNA for technology-enhanced learning (TEL), by means of four possible types of SNA applications: visualisation, analysis, simulation, and interventions. In an outlook, future directions of SNA research for TEL are provided.